Circulating microRNA-150 serum levels predict survival in patients with critical illness and sepsis. - Christoph Roderburg; Mark Luedde; David Vargas Cardenas; Mihael Vucur; David Scholten; Norbert Frey; Alexander Koch; Christian Trautwein; Frank Tacke; Tom Luedde (PLoS ONE)
Background and aims Down-regulation of miR-150 was recently linked to inflammation and bacterial infection. Furthermore, reduced serum levels of miR-150 were reported from a small cohort of patients with sepsis. We thus aimed at evaluating the diagnostic and prognostic value of miR-150 serum levels in patients with critically illness and sepsis. Methods miR-150 serum levels were analyzed in a cohort of 223 critically ill patients of which 138 fulfilled sepsis criteria and compared to 76 healthy controls. Results were correlated with clinical data and extensive sets of routine and experimental biomarkers. Results Measurements of miR-150 serum concentrations revealed only slightly reduced miR-150 serum levels in critically ill patients compared to healthy controls. Furthermore miR-150 levels did not significantly differ in critically ill patients with our without sepsis, indicating that miR-150 serum levels are not suitable for diagnostic establishment of sepsis. However, serum levels of miR-150 correlated with hepatic or renal dysfunction. Low miR-150 serum levels were associated with an unfavorable prognosis of patients, since low miR-150 serum levels predicted mortality with high diagnostic accuracy compared with established clinical scores and biomarkers. Conclusion Reduced miR-150 serum concentrations are associated with an unfavorable outcome in patients with critical illness, independent of the presence of sepsis. Besides a possible pathogenic role of miR-150 in critical illness, our study indicates a potential use of circulating miRNAs as a prognostic rather than diagnostic marker in critically ill patients.